(untitled) (Research, Society and Development, 2022)
The teaching of Science in the Early Years of Elementary School presents some individualities in relation to the other stages of teaching. One of them is in the fact that the teacher is a generalist, and almost always graduated in Pedagogy, Superior Normal or a high school teacher training course, being his/her responsibility to teach all the subjects of the basic curriculum. The present work aimed to investigate the contributions of an investigative didactic sequence following the methodological assumptions of Carvalho (1988) on the basic concepts related to sound in continuing education developed in EaD. The study is qualitative in nature and action-research type and was developed with five teachers who teach in the 3rd year of the municipal education network in the city of Mandaguari-PR through basic continuing education. All materials collected for analysis were interpreted according to Bardin’s (1977) content analysis principles and procedures. The result of our investigation points to the existence of gaps related to the basic concepts of sound, as this topic is little addressed in the skills offered well, and when they appear, they are not discussed. The conclusions of this study reveal that when professors are invited to carry out investigations, they are able to carry out analyzes in a context endowed with meanings. In this way, teachers become capable of using scientific concepts such as reading instruments, understanding of the world and meaning.